2003
DOI: 10.1097/01.lab.0000074892.53211.a5
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Based Fixative Improves Preservation of Genomic DNA and Proteins in Histoprocessing of Human Tissues

Abstract: SUMMARY:Advantageous preservation of histology and detailed cellular morphology has rendered neutral buffered formalin (NBF) the most widely used fixative in clinical pathology. Despite excellent morphology for routine diagnostics, a major drawback of NBF fixation is its detrimental effect on DNA and RNA quality. In addition to complicating analysis of genes and transcripts in complex tissues, NBF denatures proteins and thereby hampers immunohistochemical visualization of certain antigens. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 24 publications
3
54
1
2
Order By: Relevance
“…For immunohistochemical analyses, ethanol-and ZBFfixed tissue is found to be advantageous, often eliminating the need for antigen-retrieving procedures commonly performed on NBF-fixed tissue (Beckstead 1994;Ismail et al 2003;Hicks et al 2006). It has also been found that nucleic acids are better preserved in ethanol-and ZBF-fixed material than in NBF-fixed material (Gillespie et al 2002;Leiva et al 2003;Wester et al 2003;Lykidis et al 2007). In the present study, we have shown that paraffin-embedded, ethanol-or ZBF-fixed tissue is also well suited for in situ zymography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For immunohistochemical analyses, ethanol-and ZBFfixed tissue is found to be advantageous, often eliminating the need for antigen-retrieving procedures commonly performed on NBF-fixed tissue (Beckstead 1994;Ismail et al 2003;Hicks et al 2006). It has also been found that nucleic acids are better preserved in ethanol-and ZBF-fixed material than in NBF-fixed material (Gillespie et al 2002;Leiva et al 2003;Wester et al 2003;Lykidis et al 2007). In the present study, we have shown that paraffin-embedded, ethanol-or ZBF-fixed tissue is also well suited for in situ zymography.…”
Section: Discussionmentioning
confidence: 99%
“…Fixation results in a reduced volume of the tissue and hence in more-condensed structures (Wester et al 2003), which could possibly lead to more-intense signals when analyzed by in situ zymography. However, the large difference in signal intensity between fixed and frozen tissue can hardly be explained by shrinkage of the tissue alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For immunohistological evaluation, lungs were immersion-fixed in a zinc buffer containing 0.5% zinc chloride, 0.5% zinc acetate in 0.1moll -1 Tris base buffer containing 0.05% calcium acetate, pH7.4 (Wester et al, 2003), without inflation or flushing, which leads to preservation of the luminal content. To ensure proper penetration of the fixative, lungs were sliced midway and fixed for 24h at room temperature.…”
Section: Lung Immunohistochemistrymentioning
confidence: 99%
“…[8][9][10][11][12][13][14] However, studies are scarce concerning the handling of nonfixed tissue between surgery and subsequent freezing and storage at pathology departments. 15 Immediate freezing of tissue specimens after surgery and further storage at -801C generally serve as the standard procedure for the procurement of surgical specimens.…”
mentioning
confidence: 99%